Impact of the number of repeated inhalations and patient characteristics on the residual amount of inhaled laninamivir octanoate hydrate dry powder in pediatric patients with influenza - Toshiki Murasaka; Kenji Ikemura; Tomoyuki Enokiya; Yuichi Muraki; Mayumi Ikemura; Koji Terada; Takuya Iwamoto; Masahiro Okuda (BMC, 2017)
Abstract Background A dry powder inhaled formulation is used for the anti-influenza drug laninamivir octanoate hydrate (laninamivir). Although two successive inhalations (puffs) are recommended to minimize residual amounts of active ingredients, previous reports suggest that pediatric patients with low peak inspiratory flow are unable to inhale the active ingredient adequately. In the present study, we prospectively investigated the appropriate number of repeated inhalations of laninamivir dry powder and factors influencing the residual amount of ingredients in pediatric patients with influenza. Methods The study enrolled 64 patients receiving laninamivir dry powder inhaler (Inavir®) between January and March 2016 at Tsu emergency medical center/pediatric clinic and dental clinic. All patients enrolled used a laninamivir dry powder inhaler in four repeated inhalations, as instructed by a pharmacist. The residual amount of laninamivir dry powder was calculated by measuring the device weight before and after each inhalation and a residual amount of >20% was defined as an unsuccessful inhalation. Results The inadequate inhalation rate after two successive inhalations was 45%, and it decreased as number of inhalation repeats increased, reaching 23% after four successive inhalations. Peak inspiratory flow in patients with inadequate inhalation was significantly lower than that in patients with adequate inhalation, for all numbers of inhalation repeats analyzed. Receiver operating characteristic analyses indicated peak inspiratory flow cut-off values of 140, 120, 100, and 100 L/min at 1-4 successive inhalations, respectively. Conclusions The present findings suggest that a proportion of patients with low peak inspiratory flow were unable to inhale the active ingredient adequately when laninamivir dry powder inhaler was administered as two successive inhalations, as recommended in the instruction manual. Three or four repeated inhalations of laninamivir dry powder inhaler should be administered to pediatric patients with low peak inspiratory flow.